Using culture independent approaches to gain insights into human urinary tract microbiome in healthy male and female individuals - El-Alawi, Sarah Hussein (AUC Knowledge Fountain, 2011)
Here we present comprehensive insights into the diverse collection of bacterial communities that indigenously inhabit the urinary tract of healthy adult male and female individuals using cultivation independent techniques. Several studies address the importance of uncultured microbial flora that inhabits the human urinary tract in health and diseases. Thus, a deep and accurate understanding of the factors influencing this ecological niche and its microbiome is important to prevent possible infectious diseases. Genomic DNA was extracted from midstream urine samples collected from 4 adult, healthy and culture-negative male and female individuals at ages ranging from 18 to 40. Following PCR amplifications using 63F and 1387R primers for amplification of 16S rRNA genes from bacteria, 16S rRNA gene libraries were constructed using the amplified DNA fragments. From each library, we sequenced approximately 60-70 clonesÃƒÂ¢ inserts from both ends. The generated 16S rRNA gene sequences were compared against RDP II database. Separate phylogenetic analyses of the two hypervariable regions, V1-V3 and V6-V8, revealed complex bacterial profiles with predominant taxa of Prevotella, Corynebacterium, Lactobacillus, Weeksella and Gardnerella. Different bacterial genera that have been identified in urinary tract overlap the microbial communities that were formerly reported in superficial skin, gut and vaginal microbiome. Disease causing bacteria were characterized as a part of the normal flora. Inter-individual variation within the same gender was observed, and no single characteristic bacterial community was evident. However, significant variations of microbial signatures between male and female individuals were observed. 16S rRNA gene sequences assigned to bacterial genera of Streptococcus, Staphylococcus, Escherichia/Shigella and others were characterized only in urines of male subjects whereas the genera of Atopobium, Megashpera and Oligella were identified only in urines of female subjects. Moreover, the richness and evenness of bacterial flora of the urinary tract was assessed by means of alpha diversity analysis. The experiments reported in this work represent the first study of the urinary tract microbiome in healthy Egyptian male and female individuals, and should help in exploring the role of bacterial flora in health and diseases of both genders.